2004
DOI: 10.1152/ajpgi.00351.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin pathways modulate sensations induced by gastric distension in humans

Abstract: Ingested fat releases CCK, causes gastric relaxation, delays gastric emptying, and limits meal size; however, the mechanistic link among these actions has not been established. Fatty acid release of CCK is chain-length sensitive; dodecanoic acid (C12) induces greater CCK release than decanoic acid (C10). The effect of C12 or C10 on tolerance to subsequent intragastric infusion of liquid was determined in healthy subjects, with and without the CCK1 receptor antagonist dexloxiglumide. Gastric wall relaxation aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 33 publications
2
59
1
Order By: Relevance
“…It has been established that the presence of C12 in the small intestinal lumen slows gastric emptying (16,19), stimulates isolated pyloric PWs (12), increases proximal gastric relaxation (19), suppresses antral (12,23) and duodenal motility (12), and stimulates the release of CCK (12,23) and GLP-1 (12). The current study extends these observations by demonstrating that the responses are dependent on the dose of C12 administered to the small intestine and that even very low doses of C12 have potent effects.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It has been established that the presence of C12 in the small intestinal lumen slows gastric emptying (16,19), stimulates isolated pyloric PWs (12), increases proximal gastric relaxation (19), suppresses antral (12,23) and duodenal motility (12), and stimulates the release of CCK (12,23) and GLP-1 (12). The current study extends these observations by demonstrating that the responses are dependent on the dose of C12 administered to the small intestine and that even very low doses of C12 have potent effects.…”
Section: Discussionsupporting
confidence: 69%
“…Although it has been suggested that the suppressive effects of nutrients on subsequent energy intake are mediated by changes in gastrointestinal motility and gastrointestinal hormone release (19,37), the current study suggests that the stimulation of IPPWs and secretion of CCK and GLP-1 have to reach a "threshold" to result in suppression of energy intake. The motor patterns associated with infusion of C12 at 0.2 and 0.4 kcal/min are known to be associated with the slowing of gastric emptying (14), which is thought to play a role in suppressing energy intake (34).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Cholecystokinin, 17 ghrelin 18 and PYY peptide 19 levels are related to the fasting-eating cycle and to the motor function of the gastrointestinal tract. Duodenal infusion of lipids, like triglycerides 20 or fatty acids, 21 induces early satiety and causes both gastric relaxation and reduction of gastric emptying at least by the release of cholecystokinin. These relationships suggest that satiety mediated by cholecystokinin 22 and PYY 23 administration is related to motility changes of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…CCK can be induced by fatty acids with a chain length of twelve carbons or longer [5,6]. Long chain poly-unsaturated fatty acids (PUFA) have been shown to produce a large increase in CCK response [6][7][8][9][10][11][12]. After ingestion of long chain PUFA, free fatty acids (FFA) are hydrolyzed in the gut lumen and CCK is secreted [13].…”
mentioning
confidence: 99%